PENGENDALIAN KUALITAS PRODUK GULA MENGGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS DAN FAULT TREE ANALYSIS DI PT. PABRIK GULA GORONTALO - Abdullah, Moh. Rifaldi; Machmoed, Buyung R.; Rasyid, Abdul; Uloli, Hendra (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Abstract: Sugar Product Quality Control Using Failure Mode Effect Analysis and Fault Tree Analysis Methods at Pt. Gorontalo Sugar Factory This research aims to determine the types of sugar defects, factors that influence sugar product defects, and suggestions for improvements in the quality of sugar products at PT. Gorontalo Sugar Factory. The method used in this research, namely Failure Moidei and Eiffict Analysis (FMEiA), is one of the methods that functions to identify the value of failure in a system, design, process or service (seirvicei). Then Fault Tree Analysis (FTA) is a technique used to identify risks that play a role in identifying risks that play a role in failure. The results of the research were that there were three defects in white crystal sugar at PT. Gorontalo Sugar Factory, namely inappropriate sugar color, humidity, and inappropriate sugar size or what is usually called grind size. Then it was analyzed using Failure Mode Effect Analysis (FMEA) to obtain a value of RPN, purification with a value of 343, centrifugal & Drying with a value of 252, and packaging with a value of 252. Suggestions for improving sugar defect failure modes caused by machine factors are that it is best to carry out supervision SOP before carrying out the production process and the company should implement maintenance on sugar production machines so that machine performance can be maintained.